Peran Instagram Terhadap Partisipasi Masyarakat Samarinda pada Donasi Online “Tolong Menolong Lawan Covid-19” - Nuryunita; Hairunnisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instagram has many features that continue to innovate so that the application develops and switches its role to become a media for spreading information, one of the information that has been successfully shared via Instagram is the Online Donation